QUALITY OF ONE STOP SERVICE SERVICE TO SATISFACTION AND ITS IMPACT ON INSTITUTIONAL IMAGE (SURVEY AT THE IMMIGRATION OFFICE CLASS II TASIKMALAYA) - Mulyati, Sri; Kusnandar, Hasan Fahmi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
The objective of this research is to identify and analyze The Effect of ?One Stop Service?Quality Toward Applicant?s Satisfaction in Making Republic of Indonesia?s Travel Documents and Its Effect Toward The Image of Tasikmalaya Immigration Office ? Class Two Institution. The data collection was obtained through questionnaire and literature. The population in this research was Passport Applicants who applied in Tasikmalaya Immigration Office ? Class Two. The samples were determined based on 100 passport applicants. Metodology used was path analysis. In partially and simultanously, the result of research shows that ?One Stop Service? has  impact toward applicant?s satisfaction in making The Republic of Indonesia?s travel documents, and also has impact toward the impression of  Tasikmalaya Immigration Office ? Class Two.